2020
DOI: 10.1186/s13048-020-00625-8
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer subtypes and survival in relation to three comprehensive imaging parameters

Abstract: Background: Ovarian cancer (OC) is usually detected in late clinical stages, and imaging at diagnosis is crucial. Peritoneal carcinomatosis (PC) and cardio phrenic lymph nodes (CPLN) are pathological findings of computed tomography (CT) and are relevant for surgical planning. Furthermore, mammographic breast density (BD) has shown an association with OC risk and might be prognostically relevant. However, it is not known if PC, CPLN, and BD are associated with aggressive OC subtypes and impaired OC survival. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Of the 159 OC cases eligible for analysis, the distribution was as follows: 99 (60%) were classified as serous, 27 (16%) endometrioid, ten (6%) mucinous, seven (4%) clear-cell, and 12 (7%) undifferentiated/adenocarcinoma NOS, and four cases (2%) had missing information on histologic subtype in medical charts/pathology reports. As in a previously published paper on this OC cohort [ 5 ], due to the small number of cases and for purposes of clinical relevance, histological type and grade were combined into one variable with the following classification: high-grade serous tumors and endometroid tumors (all grades) were grouped, and all other histological types combined in one group (including serous type with low or unknown grade). Tumor grade was divided into low or high, with the previous intermediate grade classified as high grade.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 159 OC cases eligible for analysis, the distribution was as follows: 99 (60%) were classified as serous, 27 (16%) endometrioid, ten (6%) mucinous, seven (4%) clear-cell, and 12 (7%) undifferentiated/adenocarcinoma NOS, and four cases (2%) had missing information on histologic subtype in medical charts/pathology reports. As in a previously published paper on this OC cohort [ 5 ], due to the small number of cases and for purposes of clinical relevance, histological type and grade were combined into one variable with the following classification: high-grade serous tumors and endometroid tumors (all grades) were grouped, and all other histological types combined in one group (including serous type with low or unknown grade). Tumor grade was divided into low or high, with the previous intermediate grade classified as high grade.…”
Section: Methodsmentioning
confidence: 99%
“…A p -value < 0.05 was considered statistically significant. For sake of comparison, logistic and Cox regression analyses with CT-PCI in relation to the above stated outcomes were re-calculated and included in Table 2 together with CT short score, although previously published [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
“…The evaluation of the Peritoneal Cancer Index at the beginning of the surgery (laparotomy) was also investigated as a prognostic factor in ovarian cancer patients [ 68 , 69 , 77 , 98 , 99 ]. Several studies showed that a high CT-Peritoneal Cancer Index score is a predictor of surgical complications, lower disease-free survival and lower overall survival [ 84 , 99 , 100 , 101 ].…”
Section: Prediction Of Non-resectabilitymentioning
confidence: 99%
“…This matter suggests considering treatment options for the patient other than primary surgery [ 8 ]. Likewise, PCI estimation from a preoperative CT scan (CT-PCI) is not a component of standard guidelines for ovarian cancer diagnostics, but previous studies on CT-PCI in ovarian cancer have shown a significant relationship between CT-PCI and suboptimal surgery, postoperative complications and overall survival (OS) [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%